The role of nanocomposites against biofilm infections in humans - Varma, Anand; Warghane, Ashish; Dhiman, Neena K.; Paserkar, Neha; Upadhye, Vijay; Modi, Anupama; Saini, Rashmi (Frontiers in Cellular and Infection Microbiology, 2023)
The use of nanomaterials in several fields of science has undergone a revolution in the last few decades. It has been reported by National Institutes of Health (NIH) that sixty-five and eighty percent of all microbial and chronic illnesses, respectively, are linked to biofilm formation. Biofilm infections are answerable for at the least sixty-five % of human bacterial infections. The use of nanoparticles (NP) to eradicate bacteria that are free-floating and those that form biofilms is one of their important applications in healthcare. Nanocomposite (NC) is a multiphase stable fabric in which one of the stages has one, or 3 dimensions of much less than 100 nanometres (nm) or systems having nanoscale repeat distances between the exceptional phases that make up the material. Using NC materials to get rid of germs is a more sophisticated and effective technique to destroy bacterial biofilms. These biofilms are refractory to standard antibiotics, main to chronic infections and non-healing wounds. Materials like graphene and chitosan can be used to make several forms of NC, in addition to different metal oxides. The capacity of NC to avoid the issue of bacterial resistance is their main advantages over antibiotics. This review highlights the synthesis, characterisation, mechanism through which NC disrupts gram positive and gram negative bacterial biofilms, and their relative benefits and drawbacks. There is an urgent need to develop materials like nanocomposites with a larger spectrum of action due to the rising prevalence of human bacterial diseases that are multidrug resistant and form biofilms.